2020
DOI: 10.1002/col.22519
|View full text |Cite
|
Sign up to set email alerts
|

Colour semantics in residential interior architecture on different interior types

Abstract: Colour meaning is a challenging decision in interior architecture during the design process; however, specific meanings within different interior types have not yet been investigated. This study explored colour meaning in the context of residential interior types (eg, bedroom) under controlled conditions using 42 Munsell colours varying in hues, value, and chroma levels, with 14 adjectives (eg, comfortable, pleasant). The results demonstrate that some colours convey the same meanings (eg, vulgar) regardless of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 28 publications
4
36
1
Order By: Relevance
“…The single colour study proved that purple is not selected as much as other colours and when it is associated with a meaning in an RIT, it is associated with negative meanings more, which might be related to this phenomenon, purple is about fun and entertainment, thus should not be in a calming (or even in unquiet) house. In contrast with previous interior architecture studies, which demonstrated that green, as a single colour, is related to "home" and "calming," 7 "happiness" (for living rooms) 16 and "beautiful" and "pleasant" (for several RITs), 22 the present study's results do not reveal a lot of green colours for positive adjectives as part of paired wall colours (see Table 3 and Appendix B). These previous studies' results are based on single colours, which might be interpreted as there being a difference between single colour and paired colour associations.…”
Section: Experimental Conditionscontrasting
confidence: 99%
See 4 more Smart Citations
“…The single colour study proved that purple is not selected as much as other colours and when it is associated with a meaning in an RIT, it is associated with negative meanings more, which might be related to this phenomenon, purple is about fun and entertainment, thus should not be in a calming (or even in unquiet) house. In contrast with previous interior architecture studies, which demonstrated that green, as a single colour, is related to "home" and "calming," 7 "happiness" (for living rooms) 16 and "beautiful" and "pleasant" (for several RITs), 22 the present study's results do not reveal a lot of green colours for positive adjectives as part of paired wall colours (see Table 3 and Appendix B). These previous studies' results are based on single colours, which might be interpreted as there being a difference between single colour and paired colour associations.…”
Section: Experimental Conditionscontrasting
confidence: 99%
“…21,22 The single colour study claimed that the same colour is associated with discreet for all RITs and discreet is perceived as a positive meaning since residential interiors need to be calming and relaxing, which conflict with being loud. 22 The previous study 22 demonstrated that cold hues are related to cold and warm hues are related to warm adjectives. In contrast with this study, the present study findings show that some RITs have cold hue pairs for warm adjectives such as bathroom and toilet (see Appendix B) and vice versa (entrance, corridor, and workroom).…”
Section: Paired Coloursmentioning
confidence: 99%
See 3 more Smart Citations